GAWBS noise reduction in microstructured fibers - Elser, Dominique Alexander; Korn, Alexander; Lorenz, Stefan; Glöckl, Oliver; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (2005 European Quantum Electronics Conference, EQEC '05, 2005)
Guided Acoustic Wave Brillouin Scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. We experimentally demonstrate the reduction of GAWBS noise in microstructured fibers in comparison with standard fibers. © 2005 IEEE.
Created from Fastlane, Scopus look-up